How do you simplify (x ^ { 3} + 5) + ( 5x ^ { 3} + y + x ) (x3+5)+(5x3+y+x)?

2 Answers
Nov 8, 2017

=6x^3 + x+y +5=6x3+x+y+5

Explanation:

Combine like terms

x^3 + 5x^3 + x+y +5x3+5x3+x+y+5
=6x^3 + x+y +5=6x3+x+y+5

Nov 8, 2017

(x^3+5)+(5x^3+y+x)=color(blue)(6x^3+x+y+5(x3+5)+(5x3+y+x)=6x3+x+y+5

Explanation:

Simplify:

(x^3+5)+(5x^3+y+x)(x3+5)+(5x3+y+x)

Simplify the parenthesis.

x^3+5+5x^3+y+xx3+5+5x3+y+x

Gather like terms.

(x^3+5x^3)+x+y+5(x3+5x3)+x+y+5

Combine terms.

6x^3+x+y+56x3+x+y+5